Family-based exome sequencing identifies candidate genes related to keratoconus in Chinese families - Xu, Liyan; Yang, Kaili; Yin, Shanshan; Gu, Yuwei; Fan, Qi; Wang, Yawen; Zhao, Dongqing; Ren, Shengwei (Frontiers in Genetics, 2022)
Background: Keratoconus (KC) is a complex corneal disorder with a strong genetic component. The present study aimed to identify candidate genes related to KC in Chinese families. Methods: Family-based exome sequencing was performed in ten patients suffering from KC who belong to five families with two affected members in each. The candidate rare variants were identified with multi-step bioinformatics analysis. The STRING website was used to perform the protein interaction of the identified genes. Results: Our analyses identified 32 candidate rare variants in 13 genes by family-based exome sequencing. The molecular analyses of identified genes showed that EPCAM directly interacted with CTNNB1 of the Hippo signaling pathway and focal adhesion pathway, and directly interacted with CTNNB1, CDH1 of the WNT signaling pathway. SHROOM3 directly interacted with ROCK2, ROCK1 of the focal adhesion pathway. SYNE1 directly interacted with MUSK of the extracellular matrix organization pathway. TEK directly interacted with VEGFA, SHC1, PIK3R1, GRB2 of the focal adhesion pathway. TTN directly interacted with CAPN3 of the extracellular matrix organization pathway. Conclusion: The EPCAM, SHROOM3, SYNE1, TEK, and TTN genes were potential high-risk candidate pathogenic genes of familial KC. The findings might significantly improve our understanding of the genetic etiology of the disease, providing novel insights on KC pathogenesis.